Policy Suitability Among Three Sources of Regulations to Support the Zero Run-Off Concept on The Discharge of The Q 5 Flood in Crowded Area - Eko Widyanto, Bambang; Radhitya Akbar, Sandy; Hasan, Fuad (International Journal of Psychosocial Rehabilitation, 2020)
Several crowded area in Central Jakarta have a flood problem. The crowded area, less of infiltration area and bad drainage make this condition become worst. Several steps have used by the government, but it does not have a significant impact. An increasing of population linear with the increasing of land use changing. The land use changing from open space area which could infiltrate the rainwater change to housing, village, and another non infiltrated area. The government creates a rule to avoid flood potential which happened almost every year. Some of them are Environmental Minister Rule Number 12 2009 about The Rainfall Utilization, DKI Jakarta’s Governor Rule Number 20 2013 about Infiltration Well, and the last one is Indonesian National Standard Number 8456 2017 about Infiltration Well and Infiltration Pit of Rainfall. The three of them cannot be applicated partially, they have to applicated thoroughly. An effort to reduce runoff discharge that caused by heavy rainfall have to be started from around us. From the analysis we got the conclusion that the limit of channel area can be supported by an amount of combination between infiltration well and infiltration pit.